Disparity in Judges' Decisions Against Children Participating in Brawls (Case Study of Decision No.1/ Pid.Sus -Anak/2023/ Pn SKB and Decision No.14/ Pid.Sus -Anak/2022/ Pn CBD) - Andarini, Ayu Tri; Juhana, Ujuh (International Journal of Law Analytics, 2024)
In social life, children are often involved in crimes, one of which is fights or brawls. Therefore, serious countermeasures are needed through proper law enforcement. Currently, the application of material criminal law against fights or violence is still not aligned until disparities arise. This study uses a juridical-normative method with the aim of determining the application of material legal crimes in Decision No. 14 / Pid.Sus-Anak/2022 / Pn Cbd and Decision No.1 / Pid.Sus-Anak/2023 / Pn Skb. The results of the study show that Decision No. 14 / Pid.Sus-Anak is not appropriate, because it applies the legal basis, namely Article 358 paragraph 2 of the Criminal Code. Meanwhile, Decision No.1/pid. Sus-Anak/2023/PN SKB has been in accordance with the applicable provisions, namely applying Article 76C juncto Article 80 of Law Number 35 of 2024 concerning Child Protection by applying the principle of lex specialist derogat legi generalis.